Different Horizons of Expression in Media: The Case of Animations - Kazu, Ko (Pontificia Universidad Católica del Perú. Instituto Riva-Agüero, 2022)
This paper examines the normative constraints that mass society places on movies and artistic animation. Benjamin’s ideas on audience control in relation to technical media products are used to highlight the specific limitation of animations. Because they are entirely created by the artist (without employing preexistent elements, such as in movies), they can more easily simplify the scheme of representation-intention, and be bearers of politically or morally acceptable messages.

El ensayo aborda cuestión de los límites normativos que la sociedad de masas les impone al cine y a la animación artística. Las ideas de Benjamin en torno al control de la audiencia sobre lo producido por medios técnicos sirven de apoyo para señalar la limitación específica de las animaciones. Al ser creadas íntegramente por el artista (con exclusión de elementos preexistentes, como en el cine), es posible reducirlas más fácilmente al esquema simplificador de representación-intención y a ser portadoras de mensajes aceptables política o moralmente.
Keywords: Mass society; Technical media; Animation; Artistic cinema; Benjamin; Sociedad de masas; Medios técnicos; Animación y cine artísticos; Benjamin; https://purl.org/pe-repo/ocde/ford#6.03.01